COVID-19 and Lipid Disorders - Julius, Ulrich; Schatz, Ulrike; Tselmin, Sergey; Morawietz, Henning (Hormone and Metabolic Research, 2022)
An elevated cholesterol concentration has been suspected to increase the susceptibility for SARS-COV-2 infection. Cholesterol plays a central role in the mechanisms of the SARS-COV-2 infection. In contrast, higher HDL-cholesterol levels seem to be protective. During COVID-19 disease, LDL-cholesterol and HDL-cholesterol appear to be decreased. On the other hand, triglycerides (also in different lipoprotein fractions) were elevated. Lipoprotein(a) may increase during this disease and is most probably responsible for thromboembolic events. This lipoprotein can induce a progression of atherosclerotic lesion formation. The same is suspected for the SARS-COV-2 infection itself. COVID-19 patients are at increased risk of incident cardiovascular diseases, including cerebrovascular disorders, dysrhythmias, ischemic and non-ischemic heart disease, pericarditis, myocarditis, heart failure, and thromboembolic disorders. An ongoing lipid-lowering therapy, including lipoprotein apheresis, is recommended to be continued during the COVID-19 disease, though the impact of lipid-lowering drugs or the extracorporeal therapy on prognosis should be studied in further investigations.
Keywords: cardiovascular diseases; COVID-19; high-density lipoprotein; lipid-lowering therapy; lipoprotein(a); low-density lipoprotein